Producing consent: How environmental assessment enabled oil and gas extraction in the Qikiqtani region of Nunavut. (24th April 2020) - Bernauer, Warren
Abstract : There is now an extensive body of academic literature examining how the environmental movement contributed to the colonization of Indigenous peoples and development of capitalism in northern Canada. This paper contributes to these discussions by considering how environmental assessment (EA) helped enable hydrocarbon extraction in the Qikiqtani (Baffin Island) region of Nunavut in the 1970s and 1980s. When exploration activities began to threaten the Inuit harvesting economy, communities protested with letters and petitions. The federal government responded to Inuit resistance by referring proposed exploratory drilling and extraction to its new EA process. While Inuit won significant victories during some assessments of proposed exploratory drilling and extraction, federal EA ultimately helped create the conditions for Inuit to consent to oil extraction. EA helped impose material compromises between Inuit and hydrocarbon industries, including preferential hiring of Inuit, a reduction in the scope of proposed extraction, and the rejection of especially controversial proposals for offshore drilling. These concessions, combined with a collapse in the market for sealskins due to international boycotts, persuaded several Qikiqtani communities to support oil extraction in the 1980s. The ensuing extraction and export of oil from the High Arctic accelerated processes of colonial dispossession and reinforced colonial political dynamics. Key Messages: Environmental assessment played an important role in creating the conditions for Inuit to consent to hydrocarbon extraction in the 1980s. Environmental assessment helped persuade Inuit to consent to extraction by imposing compromises between Inuit and extractive industries. The extraction of oil before a land claim was settled undermined the ability of Inuit to capture economic benefits from extraction and negotiate ownership over offshore resources. Produire un consentement: comment l'évaluation environnementale a permis l'extraction de gaz et de pétrole dans la région Qikiqtani au Nunavut: Il existe maintenant un important corpus d'études universitaires qui examinent la façon dont le mouvement environnemental a contribué à la colonisation des Autochtones et au développement du capitalisme dans le nord du Canada. Cet article vise à contribuer à ces recherches en décrivant la façon dont les procédures d'évaluation environnementale (ÉE) ont permis l'acceptabilité de l'extraction d'hydrocarbures dans la région de Qikiqtani (île de Baffin) au Nunavut, au cours des années 1970 et 1980. Lorsque les activités de prospection ont commencé à menacer l'économie de cueillette des Inuit, les communautés ont protesté au moyen de lettres et de pétitions. Le gouvernement fédéral a répondu à la résistance des Inuit en soumettant les forages exploratoires et les projets d'extraction à son nouveau processus d'ÉE. Bien que les Inuit aient remporté d'importantes victoires contre les forages exploratoires et les projets d'extraction, l'ÉE fédérale a contribué à créer les conditions pour le consentement des Inuit à l'exploitation pétrolière. Ainsi, les procédures d'ÉE ont favorisé d'importants compromis entre les Inuit et les industries des hydrocarbures, y compris l'embauche préférentielle d'Inuit, une réduction de la portée de l'extraction proposée et le rejet de projets particulièrement controversés de forage en mer. Paradoxalement, « ces gains ponctuels », combinées à l'effondrement du marché des peaux de phoques en raison de boycottages internationaux, ont persuadé plusieurs communautés Qikiqtani d'appuyer l'extraction du pétrole durant les années 1980. En conséquence, l'extraction et l'exportation subséquentes du pétrole du Haut‐Arctique ont accéléré le phénomène de dépossession coloniale des populations Inuites.